Applying analytical hierarchy process to system quality requirements prioritization. (December 2015) - Kassab, Mohamad; Kilicay-Ergin, Nil
Abstract The order in which design decisions or tactics are incorporated within a system architecture has a significant impact on how well quality requirements are addressed in the architecture solution. Quality attributes are most often correlated; attempts to achieve one quality attribute can help or hinder the achievement of another quality relevant for the system. Thus, prioritization of quality requirements and design tactics to address these quality requirements is a useful guide for system architects. Conventional techniques of quality attribute prioritization are qualitative in nature and trade-off among design tactics are not addressed during prioritization. In this paper, analytic hierarchy process (AHP) technique is proposed to quantitatively rank design decisions and tactics while at the same time taking into consideration the interrelationships between system quality requirements and design tactics and principles. The approach is demonstrated on remote monitoring system for medical patients. The approach facilitates an objective ranking of tactics and design principles and eliminates inconsistencies between business and technical stakeholder valuation.